Nanotechnology in eco-efficient construction - Pacheco-Torgal, F. (2018)
Nanotechnology in Eco-efficient Construction, 2nd Edition is an authoritative guide illustrating the role and use of nanotechnology in the development of eco-efficient construction materials for sustainable construction. Broken down over five parts, the introductory chapters consider nanotech applications for mortars and concrete, which have high performance and self-healing ability. Part II considers nanomodified materials for pavements, structural health monitoring, ice-phobic and corrosion-free nanocoatings, as well as fire-retardant nanocoatings for protection of structural wood. Part III encompasses applications for building energy efficiency, including multifunctional architectural glazing based on highly transparent perovskite-based photovoltaics, as well as recent developments in the field of electrochromic glazing. Photocatalytic applications are the focus of Part IV, which investigates nanoparticles for pollution control, self-cleaning, and photocatalytic water purification. Finally, Part V discusses toxicity, safety handling, and the environmental impacts of nanoparticles.